2003
DOI: 10.1097/00006199-200303000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Functional Status and Correlates Following Coronary Artery Bypass Graft Surgery in Women

Abstract: Information about recovery following coronary artery bypass graft, and particularly the finding that recovery is incomplete by 6 weeks, should be incorporated into discharge planning and follow-up for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 22 publications
3
43
1
Order By: Relevance
“…Other studies have noted an improvement in PHS postoperatively, but the measurement scales and time frames have varied. 17,38,39 Scores for the Role Physical subscale also showed a significant decrease postoperatively. Although one would expect that patients would have improved physical health after surgery, the timing of data collection may have affected these results.…”
Section: Depressionmentioning
confidence: 83%
“…Other studies have noted an improvement in PHS postoperatively, but the measurement scales and time frames have varied. 17,38,39 Scores for the Role Physical subscale also showed a significant decrease postoperatively. Although one would expect that patients would have improved physical health after surgery, the timing of data collection may have affected these results.…”
Section: Depressionmentioning
confidence: 83%
“…[2][3][4][5][6][7][8] The CSS was developed to meet the need for an instrument to measure the symptom experience in the postoperative CABG population. CABG surgery has evolved to a point in which individuals of any age and with other severe comorbidities are candidates for surgery, even at a time of decreased hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Symptoms can continue to persist for even weeks after discharge. [2][3][4][5][6][7][8] Some symptoms (eg, incisional pain, fatigue, and poor appetite) are generally considered normal after CABG surgery. However, if these symptoms do not dissipate over time as expected, they may be indicative of actual or impending problems.…”
mentioning
confidence: 99%
“…Patterns of disability using this newer disability definition, difficulty with ADL and IADL, during the first 6 weeks of recovery after a cardiac event have found that 43% of older MI participants had substantial disability (van Jaarsveld, Sanderman, Miedema, Ranchor, & Kempen, 2001) and women after CABS do not completely recover their baseline function in personal care, household activity, volunteer work, and taking care of another (DiMattio & Tulman, 2003). Measurement of disability as difficulty has challenged previous findings.…”
Section: Patterns Of Disability After a Cardiac Eventmentioning
confidence: 99%